Functions to containerized microservice continuous delivery [to AWS App Runner with Fast API]. (Pragmatic AI Solutions, 2022)
Learn to deploy containerized Microservices using Cloud9, ECR, App Runner and FastAPI automatically with AWS Code 00:00 0:37 Continuous Delivery Architecture 01:06 AWS App Runner 01:41 Building Containerized Microservices with FastAPI 03:22 Pinning requirements.txt to a specific version 06:10 Running FastAPI 10:40 Setup ECR 14:19 Setup ECR with AWS App Runner 16:10 Create containerized Flask API Microservice in Github Codespaces 18:54 Testing Swagger UI in Github Codespaces 20:11 Verify FastAPI Microservice in AWS App Runner 22:20 Setup AWS Code Build for Continuous Deployment with App Runner 30:12 Architectural Overview of Continuous Deployment 32:35 Verify Continuous Deployment with AWS Code Build and App Runner.